Expansion of the exotic macroalga Batophora occidentalis in Posidonia oceanica meadows and other native benthic habitats - Andrea Anton; Silvia Paoletti; Lidia Cucala-Garcia; Carlos Morell; Sara Muñiz-Quintana (PLoS ONE, 2026)
Marine invasive macroalgae can be detrimental to native ecosystems. The exotic green macroalga Batophora occidentalis was first reported in 2020 in Estany des Peix lagoon in Formentera (Spain). In 2023 and 2024, our surveys revealed that it had spread to 100% of the surveyed locations within the lagoon. In 2024, B. occidentalis, reached an average cover of 30% in Cymodocea nodosa meadows and 26% in Caulerpa prolifera meadows, with respective biomasses of 52 g m ⁻ 2 and 44 g m ⁻ 2 , making it the most abundant macrophyte in these two native benthic habitats. We also found exotic B. occidentalis growing epiphytically on the leaves and rhizomes of Posidonia oceanica within the lagoon, with an average cover of 12% in 2023 and 16% in 2024, and a biomass of 3 g m ⁻ 2 in 2024. Notably, it covered nearly 25% of the P. oceanica leaf surface and reached up to five times the weight of individual leaves. Alarmingly, we report the presence of a B. occidentalis specimen on a P. oceanica shoot in a nearby meadow outside the lagoon, signalling a potential spread beyond its current range. Additionally, the exotic macroalgae colonized various natural and hard substrates, including boat hulls, as it was growing on nearly 20% of boats anchored in the only marina in the lagoon. With this study, we aim to encourage prompt action from local and regional governments. We may be witnessing the early stages of a broader expansion of this exotic alga, highlighting a critical moment to implement early management measures such as monitoring, and, where possible, containment within the lagoon.